The accessible Web portal B-Navigator: prototype evaluation - Díaz, Francisco Javier (2005)
The accessible Web portal B-Navigator constitutes a digital medium between visually impaired and blind people, and Internet. This portal offers two basic functions: firstly, it "makes accessible" the Web page solicited by the user applying the accessibility norms recommended by international organizations; secondly, it "integrates" different adaptations like screen magnifiers, document readers, which are incorporated automatically in the Web page visited although they were not been provided in the original design. This article presents an evaluation performed to a prototype of the B-Navigator portal, where twenty users with different visual disability levels have participated. It was mounted in the Braille Library of La Plata city, where an Internet environment was simulated. The evaluation results were very useful. The users selection was adequately and lets us to test the performance, the assistance level, the efficiency of the human-computer interaction, the capacity of adaptation of the portal. In this manner, the quality of the product was analyzed. This work was a great incentive to finish the portal development and to publish it definitively in the Web in order to be used by all of us without discriminations.